Bioengineered 3D Models to Recapitulate Tissue Fibrosis. Issue 6 (June 2020) - Sacchi, Marta; Bansal, Ruchi; Rouwkema, Jeroen
Abstract : Fibrosis, characterized by progressive tissue stiffening resulting in organ failure, is a growing health problem affecting millions of people worldwide. Currently, therapeutic options for tissue fibrosis are severely limited and organ transplantation is the only effective treatment for the end-stage fibrotic diseases with inherent limitations. Recent advancements in engineered 3D in vitro human disease mimic models, recapitulating the tissue pathophysiology, have provided unique state-of-the-art platforms for: (i) understanding the biological mechanisms involved in the disease pathogenesis; and (ii) high-throughput and reproducible drug screening. This review focuses on the recent multidisciplinary developments made towards advanced 3D biomimetic fibrotic tissue (liver, kidney, and lung) models that combine highly precision manufacturing techniques with high cellular functionality and biophysical (mechanical) properties. Highlights: Fibrosis, characterized by an excessive ECM deposition resulting in organ failure, represents a growing health problem worldwide. Where development of therapies is hampered due to disease complexity, recent advances in fibrotic tissue models generate promising platforms for understanding the disease and screening of new drugs. Self-assembled 3D cultures are phenotypically stable models for studying fundamental cell–cell and cell–matrix interactions, amendable for high-throughput drug screening. 3D-bioprinted organotypic tissues resemble 3D spatial cellular organization and replicate key fibrogenic features. Organ-on-a-chip and microfluidic systems combine 3D culture with controlled mechanical microenvironment, and recapitulate tissue fibrosis physiology. Highly physiological ex vivo human tissue-based models closely mimic fibrotic tissues organization and composition.